Stochastic evaluation of quasi-zero stiffness magnetic spring using a reluctance-corrected analytical model - Jung, Jaehwan; Yoon, Kyung Taek; Choi, Young Man (Precision Engineering, 2024)
—In state of the art high-precision motion systems, which utilize magnetic levitation, a quasi-zero stiffness gravity compensation is one of the essentials to improve dynamic performance, eliminate position dependency and thus simplify controller design. Special configurations of permanent magnets, such as Halbach magnet arrays, can realize magnetic levitation as a form of magnetic spring. However, unlike conventional permanent magnet machines with large stiffness, the quasi-zero stiffness magnetic spring requires higher modeling accuracy for force estimation, which is affected by the nonlinear reluctance effect of permanent magnets. In this study, we propose an accurate magnetic modeling method for the quasi-zero stiffness magnetic spring. By correcting the reluctance effect of magnets, the proposed magnetic model achieves superior accuracy estimating levitation force and stiffness to the conventional surface current model. Using the reluctance-corrected magnetic model, tolerance analysis was performed to identify dominant geometric parameters affecting the uncertainty of the Halbach array magnetic spring performance. A Monte-Carlo simulation was used to estimate the overall tolerance of magnetic forces and stiffness. The experimental results fit in the tolerances.
Keywords: Halbach magnet array; High-precision motion; Magnetic models; Magnetic spring; MonteCarlo methods; Quasi-zero stiffness; State of the art; Stochastic evaluations; Tolerance analysis; —gravity compensator; Halbach magnet array; Magnetic model; Magnetic spring; Monte-Carlo methods; Tolerance analysis; —Gravity compensator